1969
DOI: 10.1002/ange.19690811015
|View full text |Cite
|
Sign up to set email alerts
|

Assoziation im festen Zustand von Bis(trimethylsilyl)amidolithium und Methyltrimethylsilanolatoberyllium

Abstract: Das IH-NMR-Spektrum (CD3COCD3) weist symmetrisch zu T = 6.33 zwei aus je drei verbreiterten Banden bestehende Signalgruppen auf. Daraus kann ebenfalls auf die cis-Anordnung der CO-und PH3-Liganden geschlossen werden [***I.Beim tmns-Isomeren wtiren ntlmlich zwei PH3-Gruppen gleich, die dritte wahrscheinlich verschieden abgeschirmt.was ein anderes Erscheinungsbild des Spektrums zur Folge htltte. Die Abstande der zueinander symmetrischen Banden sind 338, 308 und 282 Hz, ihre Intensittiten verhalten sich wie 1 :0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
6

Year Published

1969
1969
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 2 publications
3
20
0
6
Order By: Relevance
“…The structures of the [MLi 7 (m 8 -O)(m,m¢-hpp) 6 ] + cations (M = Mn, Co, Zn) are essentially identical, hence only 4 will be discussed in detail. Key bond lengths for 2, 4 and 5 are shown for comparison in Table 1, and the structures of 2 and 5 are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of the [MLi 7 (m 8 -O)(m,m¢-hpp) 6 ] + cations (M = Mn, Co, Zn) are essentially identical, hence only 4 will be discussed in detail. Key bond lengths for 2, 4 and 5 are shown for comparison in Table 1, and the structures of 2 and 5 are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative synthesis of [2][3], using the same amounts of each reagent but with the suspension of MnCl 2 in toluene containing 50 mL of degassed water, was also accomplished (0.06 g, 36% isolated yield). Elemental analysis for C 72 H 162 N 23 OSi 10 ClLi 7 Mn: calculated C 48.42;H 9.14,N 18.04;found C 48.11,H 8.99,N 17.67 (6) • , V = 11829.9(13) Å 3 , T = 100(1) K, Z = 4, 21119 reflections collected, 7584 independent reflections (R int = 0.0906), 99.7% completeness to q = 21.00…”
Section: Synthesis Of [2][3]mentioning
confidence: 99%
“…[44] Somit ist 1 das erste der nützlichen Alkalimetallamide, das kristallographisch charakterisiert wurde (siehe Tabelle 3 für eine Zusammenfassung der im Manuskript angesprochenen Molekülstrukturen und Tabelle 4 für deren wichtigste Bindungsparameter). Eine detailliertere Untersuchung durch Atwood und Mitarbeiter fast 10 Jahre später [45] belegte, dass der zentrale Li 3 N 3 -Ring mit einer Abweichung von 0.01 planar ist [Li-N-Bindungslänge von 2.00 (2) (2)8].…”
Section: Autorunclassified
“…The first reaction combined LiHMDS, LiCl, and the chiral diamine N,N,N',N'-(1R,2R)-tetramethylcyclohexane-1,2-diamine ((R,R)-TMCDA), initially in a 1:1:1 stoichiometric ratio in hexane solution. A small crop of X-ray-quality crystalline material was afforded from this mixture after 24 h. X-ray crystallographic analysis [9] revealed that despite the equimolar ratio of LiHMDS and LiCl in the reaction, crystallization of the lithium lithiate…”
Section: (Oh)]mentioning
confidence: 99%
“…This unexpected entity must be considered in the context of the well-developed structural chemistry of LiHMDS species. Donor-free LiHMDS exists as a trimer in the solid state, [11] whilst solution studies by Collum and Lucht reveal that an equilibrium exists between a dimeric and a tetrameric species. [12] To the best of our knowledge, a discrete ten-atom Li 5 N 5 ring (or indeed of any lithium anion combination) has not been reported to date.…”
Section: (Oh)]mentioning
confidence: 99%